Silence: the mystery of wholeness - Sardello, Robert J. (Goldenstone Press [u.a.], 2008)
A meditation on silence -- The guardians of silence -- Entering the silence -- Relating within silence -- The healing power of silence -- Silence in daily living -- Making a clearing for silence -- The silence of the heart -- Silence, prayer, and meditation